Simple and sensitive detection of quercetin antioxidant by teos coated magnetic fe2o3 core-shell - Şenocak, Ahmet (Turkish Chemical Society, 2020)
In this study, ?-Fe2O3 and tetraethyl orthosilicate (TEOS) coated Fe2O3 (TEOS@Fe2O3) was synthesized by the sol-gel method. The morphological properties and electrochemical detection of quercetin antioxidant with Fe2O3 and TEOS@Fe2O3 nanomaterials were evaluated. TEOS@Fe2O3 material was modified on a glassy carbon electrode (GCE) for the detection of quercetin with a linear range of 1.0-9.0 ?M by square wave voltammetry (SWV). TEOS@Fe2O3/GCE sensor ca 1.6 and 2.5 times more sensitive than Fe2O3/GCE and GCE. The quantification (LOQ) and detection (LOD) limits were found to be 306 and 92 nM for quercetin antioxidant on the TEOS@Fe 2O3 modified electrode. Quercetin was also determined in an apple tea sample with a standard addition method, and the recovery of quercetin was obtained to be 104.16% and 106.04%. The results obtained from this study show that the TEOS@Fe 2O3 modified electrode examined as a voltammetric sensor was found to be sensitive and straightforward to quercetin. © 2020 Elsevier B.V., All rights reserved.
Keywords: Electrochemical sensor, TEOS; Magnetic nanoparticle; Quercetin antioxidant